1997
DOI: 10.1002/(sici)1096-9071(199708)52:4<436::aid-jmv16>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus antibody responses among patients with incident cervical carcinoma

Abstract: The human papillomavirus (HPV) is recognized as a major cause of cervical cancer precursor lesions. HPV serology is a key method in the continuing elucidation of the importance of HPV exposure for cancer development and in predicting HPV-associated diseases. To extend previous HPV serological studies on cervical cancer, serum samples from a consecutive series of 216 women with incident untreated cervical carcinoma and 243 age- and sex-matched healthy blood donors were evaluated for the presence of antibodies a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…Significant associations for E6 and E7 antibodies for high‐risk types other than HPV16 and 18 extend the findings from other cross‐sectional studies reporting associations between HPV16 E6 and/or HPV16 E7 and risk of cervical and anal cancer . However, many of these studies were not able to stratify by HPV DNA type in the tumor.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Significant associations for E6 and E7 antibodies for high‐risk types other than HPV16 and 18 extend the findings from other cross‐sectional studies reporting associations between HPV16 E6 and/or HPV16 E7 and risk of cervical and anal cancer . However, many of these studies were not able to stratify by HPV DNA type in the tumor.…”
Section: Discussionsupporting
confidence: 66%
“…The immune response to L1, the main component of the HPV capsid, has been widely studied in cross‐sectional and prospective studies, albeit using different serological assays, and is considered a marker of cumulative exposure to HPV infection, rather than of HPV‐related malignancy. In the present study, HPV16 L1 and HPV18 L1 were both significantly associated with cancer risk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several prospective studies have shown that seropositivity for HPV-16 increases the risk for future development of cervical cancer (Lehtinen et al, 1996 ;Shah et al, 1997 ;Dillner et al, 1997 ;Vonka et al, 1999) and other anogenital cancers (Bjo$ rge et al, 1997), and there are also studies that have found seropositivity to HPV-18 and -33 to be associated with invasive cervical cancer (Dillner et al, 1997 ;Wang et al, 1997). However, since the different oncogenic HPV types are similarly transmitted and since seropositivities for the different oncogenic HPV types thus are strongly associated with each other (Dillner et al, 1996), the possibility exists that the excess risks seen may be secondary to the excess risks associated with other HPV types.…”
Section: Introductionmentioning
confidence: 99%
“…The preponderance of epidemiologic studies implicates a sexually passed agent as the primary risk factor for intraepithelial and invasive neoplasms of the uterine cervix [23][24][25][26][27]. Presently, human papilloma virus (HPV) is the prime suspect, particularly the so-called oncogenic types, including types 16 and 18, and possibly types 31, 35, 45, and other higher types [28][29][30][31][32][33][34][35][36][37]. But other sexually transmissible infections [38][39][40][41][42][43][44][45][46][47] and environmental and hereditary factors, or lack thereof, may ultimately prove to be important for initiation and progression of these neoplasms [48][49][50][51][52][53][54][55].…”
Section: Uterine Cervix Carcinomamentioning
confidence: 99%